Macrofauna e atributos físicos em sistemas de uso e manejo do solo. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Excessive management tends to negatively affect physical conditions, macrofauna and soil microbial biomass. Physical and biological attributes are used as parameters to assess soil quality in different soil uses and managements. The objective of this work was to evaluate the epiedaphic and euedaphic macrofauna and the biological and physical attributes in different land use and management systems. Traps for collecting epiedaphic organisms, in Ponta Grossa-PR, were inserted in crops, pastures and forests. Shannon diversity, Pielou uniformity, richness and principal components analysis were calculated. In the study conducted in Ponta Grossa-PR, 889 individuals were captured, distributed in 18 taxonomic groups. There was greater diversity of individuals in the area of natural vegetation, with 17 taxonomic groups, followed by the pasture area with 14, and the crop with 11. 13 taxonomic groups were found in the area of secondary forest, crop with 11 and pasture with 9 individuals. The highest diversity value evaluated by the Shannon index was observed in secondary forest presenting a value of 0.75 followed by 0.57 and 0.46 for pasture and crop respectively. The pielou and/or homogeneity index obtained values of 0.44 for crop, pasture 0.60 and 0.67 for secondary forest. There is a correlation between the groups and the use and management, with an increase or decrease in the number of individuals according to the soil conservation scale of use and management, except for the Orthoptera group. Soil collections in Tibagi-PR were carried out in an ecological and conventional pasture management system, with soil samples being taken at 6 points in each system, density, granulometry, aggregate stability, macrofauna and biomass carbon analyzes were performed microbial. For the experiment in Tibagi-PR, soil density showed, at a depth of 5-10 cm, a significant interaction between time of adoption and systems. The systems were the same at T0 and MEP showed higher soil density at T1. For biomass carbon, at 0-5 cm depth, there was a significant interaction between time of adoption and systems. The systems were the same at T0 and MEP showed higher soil carbon at T1. The weighted average diameter, at a depth of 5-10 cm, was significant between the times of adoption of the systems. There was a significant difference over time for the depth of 5-10 cm. For depths of 0-5cm, there was a significant difference for macrofauna between systems and for time of adoption. In the MEP, the presence of Oligochaetes and Isopterans, which can be considered beneficial organisms, in addition to a greater diversity of forages, deserves to be highlighted. Thus, the adoption of MEP presented positive results regarding soil biology and negative results regarding soil physics.
Keywords: fauna edáfica; atributos do solo; sistemas de manejo; biodiversidade; edaphic fauna; soil attributes; management systems; biodiversity; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA